KOLASE PERMAINAN TRADISIONAL UNTUK MEMFASILITASI PEMBELAJARAN SENI RUPA ANAK USIA DINI - Aini Loita; Nuraly Ma’sum Aprily; Denden Setiaji; Tasya Nur Ramdhani (Universitas Pendidikan Indonesia (UPI), 2022)
This research is motivated by problems in early childhood art learning that arise in the field related to the limited availability of teaching materials based on local wisdom, or even almost non-existent. The learning process in PAUD will be carried out optimally if there are components that are relevant and useful for learning, in this case teaching materials with local content. The aim of this research is to develop visual arts teaching materials in the form of collage teaching materials based on local wisdom of traditional games according to field needs for children aged 5-6 years. The method used in this study is the development method with an EDR design based on the McKenney EDR model, which is divided into three parts, namely, analysis and exploration, design and construction, evaluation and reflection. Data collection techniques are observation, interviews, questionnaires, and expert validation. This article presents how to design and construct teaching materials for traditional game collages with the steps for making them. Starting from curriculum analysis covering development programs, core competencies, basic competencies, achievement indicators, as well as learning objectives, expert validation and product design. It is hoped that this traditional game collage teaching material can provide an overview of collage teaching materials as part of a practical and valid learning tool to assist teachers in implementing art learning based on local wisdom of traditional games which can stimulate various child developments optimally. Penelitian ini dilatar belakangi permasalahan pembelajaran seni rupa anak usia dini yang muncul di lapangan terkait ketersediaan bahan ajar berbasis kearifan lokal yang terbatas bahkan nyaris tidak tersedia. Proses pembelajaran di PAUD akan terlaksana secara optimal apabila terdapat komponen yang relevan dan berguna untuk pembelajaran, dalam hal ini bahan ajar dengan muatan lokal. Tujuan dari penelitian ini adalah untuk mengembangkan bahan ajar seni rupa berupa bahan ajar kolase yang berbasis kearifan lokal permainan tradisional yang sesuai dengan kebutuhan lapangan untuk anak usia 5-6 tahun. Metode yang digunakan dalam penelitian ini adalah metode pengembangan dengan desain EDR yang didasarkan pada model EDR McKenney, yang terbagi menjadi tiga bagian yaitu, analisis dan eksplorasi, desain dan konstruksi, evaluasi dan refleksi. Teknik pengumpulan data adalah observasi, wawancara, angket, dan validasi ahli. Pada artikel ini disajikan bagaimana desain dan kontruksi perancangan bahan ajar kolase permainan tradisional dengan langkah-langkah pembuatannya. Dimulai dari analisis kurikulum meliputi program pengembangan, kompetensi inti, kompetensi dasar, indikator pencapaian, serta tujuan pembelajaran, validasi ahli dan perancangan produk. Bahan ajar kolase permainan tradisional ini diharapkan dapat memberikan gambaran bahan ajar kolase sebagai bagian perangkat pembelajaran yang praktis dan valid untuk membantu guru dalam melaksanakan pembelajaran seni rupa berbasis kearifan lokal permainan tradisional yang dapat menstimulasi berbagai tumbuh kembang anak dengan optimal.